EKSPLORASI NILAI MATEMATIKA PADA TINGKATAN TELUR MAULID CIKOANG TAKALAR - Firdaus, Andi Mulawakkan; Syamsinar, Syamsinar (TRANSFORMASI, 2024)
Mathematics as part of learning, requires daily life such as culture to be used as a learning source. One of the Takalar cultures is the celebration of Cikoang mawlid, also cannot be separated from mathematics. This celebration contains mathematical concepts, especially at the egg level. The aim of this research is to explore mathematical concepts found at the Cikoang mawlid egg level in Takalar district. This research uses an ethnographic approach. Data collection was carried out using literature review, observation and interview techniques. The results showed that at the egg level, the concept of arithmetic sequences and series was found. Furthermore, this concept can be developed to become part of mathematics learning.